Water-soluble trehalose glycolipids show superior Mincle binding and signaling but impaired phagocytosis and IL-1β production - Manthrirathna, M. A. Thathsaranie P.; Dangerfield, Emma M.; Ishizuka, Shigenari; Woods, Aodhamair; Luong, Brenda S.; Yamasaki, Sho; Timmer, Mattie S. M.; Stocker, Bridget L. (Frontiers in Molecular Biosciences, 2022)
The tremendous potential of trehalose glycolipids as vaccine adjuvants has incentivized the study of how the structures of these ligands relate to their Mincle-mediated agonist activities. Despite this, structure-activity work in the field has been largely empirical, and less is known about how Mincle-independent pathways might be affected by different trehalose glycolipids, and whether Mincle binding by itself can serve as a proxy for adjuvanticity. There is also much demand for more water-soluble Mincle ligands. To address this need, we prepared polyethylene glycol modified trehalose glycolipids (PEG-TGLs) with enhanced water solubility and strong murine Mincle (mMincle) binding and signaling. However, only modest cytokine and chemokine responses were observed upon the treatment of GM-CSF treated bone-marrow cells with the PEG-TGLs. Notability, no IL-1β was observed. Using RNA-Seq analysis and a representative PEG-TGL, we determined that the more water-soluble adducts were less able to activate phagocytic pathways, and hence, failed to induce IL-1β production. Taken together, our data suggests that in addition to strong Mincle binding, which is a pre-requisite for Mincle-mediated cellular responses, the physical presentation of trehalose glycolipids in colloidal form is required for inflammasome activation, and hence, a strong inflammatory immune response.